BiF3Incorporation in Na/Ba Mixed Network Modifier Fluoride-Phosphate Glasses: Structural Studies by Solid-State NMR and Raman Spectroscopies - Galleani, Gustavo; Bradtmüller, Henrik; Fares, Hssen [UNESP]; Santagneli, Silvia Helena [UNESP]; Nalin, Marcelo [UNESP]; Eckert, Hellmut (American Chemical Society (ACS), 2020)
Bismuth-containing rare-earth codoped fluoride phosphate glasses are promising materials for superbroadband near-infrared (NIR) emission with potential applications in optical amplification. To elucidate their structural organization, this contribution develops a comprehensive multinuclear solid-state single and 31P/19F double resonance NMR strategy, applied to glasses in the system (BiF3)y(50NaPO3-20Ba(PO3)2-20NaF-10BaF2)100-y (y = 0, 5, 10, 20, 30, 40). To separately assess the influence of bismuth and fluorine constituents on the network structure, an additional set of (NaPO3)50-2x(Ba(PO3)2)20-x(NaF)20+2x(BaF2)10+x (x = 0, 2.5, 5.0, 7.5) glasses was also investigated. Introduction of alkali fluoride ions into phosphate glasses is shown to follow a new network modification scheme involving depolymerization of polyphosphate chains under the formation of F-bonded fluorophosphate units. However, a significant part of the fluoride stays separate, interacting exclusively with metal-ion species. 23Na MAS and 23Na{31P} double resonance NMR results are consistent with a local sodium ion environment dominated by phosphate ions in the Bi-free system, whereas in the BiF3-containing glasses, the successive reduction of the dipolar second moment M2(Na-P) with increasing BiF3 content reflects the expected dilution effect, accompanied by increasing competition of the fluoride ions for ligation with the Na+ ions.